Odpowiedzialność egzystencjalna jako fundament odpowiedzialności w etyce społeczno-gospodarczej - Mizdrak, Inga (Annales. Etyka w Życiu Gospodarczym, 2020)
Purpose: On the one hand, the aim of this paper is to highlight the importance of responsibility in its rudimentary aspect. On the other, it reflects on the disquieting phenomena that occur in socio-economic practice which can be traced to various origins and which can lead to numerous deficiencies in public administration and business activities. Method: The study was carried out by analyzing the rudimentary aspects of responsibility from the ontological-ethical perspective. Results: It was established that individuals, who are a part of organizational structures, should not only recognize and fulfill various types of responsibility that result from a variety of tasks and goals but more importantly, they should acknowledge the existence of a core responsibility within the organization, which extends beyond legal acts and statutes. The complex nature of the issue of responsibility, as well as its ethical-social implications in the scope of ontological-existential debate, were recognized. Conclusions: The studies conducted show that responsibility plays a key role in defining modern management trends and socio-economic problems. The role of responsibility in business entities and public administration fulfilling tasks, goals and challenges is indisputable. Contribution to the discipline: The conducted analyses further clarify the nature and the basic function of responsibility both in the entity and in socio-economic relations.